Optimalisasi Pembelajaran Akhlak Untuk Mencegah Bullying Melalui Pendekatan Model Kurt Lewin - Yurika Nur Utami; Nabila Husna; Alifah Hasna; Lulu Mala Bonita (PT. Pusmedia Group Indonesia, 2025)
Bullying in elementary school environment is a serious challenge for students in terms of character formation with noble morals. This study aims to optimize moral learning in SDIT Sirojut Taqwa as a preventive strategy for bullying behavior. In this study, the behavioral change approach from the Kurt Lewin Model (unfreezing-changing-refreezing) was used. Through observation, interviews, and documentation, this study uses a descriptive qualitative method. The unfreezing stage is carried out through case studies, video shows, and discussions by raising students' and teachers' awareness of the impact of bullying. The changing stage is implemented through the integration of moral values in thematic learning and daily habits. In addition, the implementation is also carried out through a religious guidance program. The refreezing stage involves collaboration between teachers and parents in monitoring, as well as providing rewards for positive behavior as well as ongoing evaluation. This approach, according to the research results, is effective in creating a religious, safe, and more empathetic school environment. This study confirms the conclusion that optimizing moral learning based on the Kurt Lewin Model on an ongoing basis can strengthen positive character and reduce the potential for bullying behavior in students. Keywords: Bullying; Moral Learning; Kurt Lewin's Model